Penerapan Extreme Programming dalam Pengembangan Sistem E-Tiket Berbasis Web pada Objek Wisata Lokal - Tarso Tarso; Evi Martiani; Osi Krismonika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
A local tourism object serving as the research site still relies on a manual ticketing system, which has caused several operational issues including long queues at the entrance, transaction recording errors, and limited access to real-time visitor data that hinders management decision-making. This study aims to develop a web-based e-ticketing system as a solution to these problems by implementing the Extreme Programming (XP) method. XP was selected because it supports iterative and adaptive software development in response to changing user requirements through four main phases: planning, design, coding, and testing. The system was developed using PHP Native as the server-side programming language, MySQL as the database management system, and HTML, CSS, and JavaScript for the user interface, along with a ticket booking feature and WhatsApp-based notification. Testing was conducted using Black Box Testing to verify system functionality and User Acceptance Testing (UAT) to measure the level of end-user acceptance. Black Box Testing results on five main system functions showed that all features performed according to functional requirements with a 100% success rate. UAT results involving 15 respondents consisting of tourism managers and visitors yielded an average feasibility score of 88.03%, categorized as